The Effect of Polymer-Cement Stabilization on the Unconfined Compressive Strength of Liquefiable Soils - Ali Ateş (International Journal of Polymer Science)
Soil stabilization has been widely used as an alternative to substitute the lack of suitable material on site. The use of nontraditional chemical stabilizers in soil improvement is growing daily. In this study a laboratory experiment was conducted to evaluate the effects of waterborne polymer on unconfined compression strength and to study the effect of cement grout on pre-venting of liquefiable sandy soils. The laboratory tests were performed including grain size of sandy soil, unit weight, ultrasonic pulse velocity, and unconfined compressive strength test. The sand and various amounts of polymer (1%, 2%, 3%, and 4%) and cement (10%, 20%, 30%, and 40%) were mixed with all of them into dough using mechanical kneader in laboratory conditions. Grouting experiment is performed with a cylindrical mould of  mm. The samples were subjected to unconfined compression tests to determine their strength after 7 and 14 days of curing. The results of the tests indicated that the waterborne polymer significantly improved the unconfined compression strength of sandy soils which have susceptibility of liquefaction.